Unpacking mathematical gender stereotypes: trends and directions from 25 years of research - Nurlu, Özge (Frontiers in Psychology, 2025)
Gender norms shape multiple domains, including mathematics—long framed as a male-dominated field—thereby fostering pervasive mathematical gender stereotypes (MGS) that affect individuals’ participation and achievement. This study aims to systematically synthesize empirical research published between 1999 and 2024, indexed in Web of Science, written in English, and available in full text. Only articles explicitly examining MGS were included; studies focused on broader STEM stereotypes, non-English publications, records without full-text access, and papers outside the specified time window were excluded. Limitations include the absence of protocol pre-registration—although inclusion/exclusion criteria and the analysis plan were specified in writing prior to the search and PRISMA 2020 guidelines were followed—and the unavoidable subjectivity in interpretation and categorization despite established inter-coder reliability. Analyses indicate that most studies are situated in psychology, frequently employ experimental designs, and primarily sample university students. Surveys dominate data collection, and parametric inferential statistics are commonly used. Geographically, the literature is concentrated in Western countries—particularly the United States and Germany—with limited contributions from the Global South. Publication counts fluctuate over time, with notable peaks in 2012 and 2022. Conceptually, the literature converges on two principal axes: (i) belief/domain-ownership formulations centered on male superiority and (ii) process-based formulations centered on ST. Less frequently examined yet theoretically informative extensions include endorsement, internalization, counter-stereotypic role models, and stereotype lift. Across qualitative, descriptive, correlational, mediation, meta-analytic, and experimental evidence, findings consistently cluster around these axes, with stereotype endorsement and MGS occupying central positions. Taken together, the results underscore the need for future research that is more interdisciplinary, cross-cultural, and methodologically diverse to more comprehensively address MGS.